2011
DOI: 10.1093/carcin/bgr083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of RECK gene polymorphisms and environmental factors on oral cancer susceptibility and clinicopathologic characteristics in Taiwan

Abstract: Oral cancer is the fourth common male cancer and causally associated with environmental carcinogens in Taiwan. The reversion-inducing-cysteine-rich protein with Kazal motifs (RECK) has a significant effect on tumorigenesis by limiting angiogenesis and invasion of tumors through the extracellular matrix. RECK downregulation has been confirmed in many human cancers and associated with lymph node metastasis clinically. In the present hospital-based case-controlled study, the demographic, RECK genotype and clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…The adjusted odds ratios (AORs) with 95% confidence intervals (CIs) for the association between genotype frequencies and the risk of OSCC plus clinicopathologic characteristics were estimated by multiple logistic regression models after controlling for other covariates. The interactions of RAGE gene polymorphisms with each demographic characteristic were evaluated as described previously (Chung et al 2011). In brief, we fitted a logistic regression model with main effects (RAGE genetic polymorphism, smoking status, alcohol drinking status, and betel quid chewing status) as well as an interaction term between them (RAGE genotypes × demographic characteristic), as comparing the model against a model with only the main effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjusted odds ratios (AORs) with 95% confidence intervals (CIs) for the association between genotype frequencies and the risk of OSCC plus clinicopathologic characteristics were estimated by multiple logistic regression models after controlling for other covariates. The interactions of RAGE gene polymorphisms with each demographic characteristic were evaluated as described previously (Chung et al 2011). In brief, we fitted a logistic regression model with main effects (RAGE genetic polymorphism, smoking status, alcohol drinking status, and betel quid chewing status) as well as an interaction term between them (RAGE genotypes × demographic characteristic), as comparing the model against a model with only the main effects.…”
Section: Discussionmentioning
confidence: 99%
“…To date, interactions between polymorphisms of many susceptibility genes and exposure of environmental carcinogens have been reported to affect the risk for OSCC (Chung et al 2011;Supic et al 2011;Bharti et al 2013). Epidemiologic investigations have shown that tobacco smoking and betel nut chewing are 2 of the major risk factors for OSCC development (Awang 1988;Scully and Bagan 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest single nucleotide polymorphisms are important in mediating an individual's susceptibility to varous types of cancers [25]. Based on testability that can be analyzed from blood samples, these SNPs are attractive molecular markers for translational studies.…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC), a common malignant cancer in the head and neck region, is the fourth most common male cancer and the sixth leading cause of cancer death in Taiwan [1]. The development of OSCC is a multistep process requiring the accumulation of multiple genetic alterations, affected by a patient's genetic predisposition and by environmental influences, including alcohol and tobacco consumption, betel-quid chewing, chronic inflammation, and viral infection [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The development of OSCC is a multistep process requiring the accumulation of multiple genetic alterations, affected by a patient's genetic predisposition and by environmental influences, including alcohol and tobacco consumption, betel-quid chewing, chronic inflammation, and viral infection [1][2][3][4][5][6]. Expression of a gene may be affected by a single-nucleotide polymorphism (SNP) located within the promoter or other regulatory regions of the gene, and the production or activity of its translated protein is further modulated.…”
Section: Introductionmentioning
confidence: 99%